EFISIENSI PRODUKSI DAN PENDAPATAN USAHATANI CABAI MERAH DI KECAMATAN METRO KIBANG KABUPATEN LAMPUNG TIMUR: PENDEKATAN FUNGSI PRODUKSI FRONTIER - Siti Hardiyanti Chonani; Fembriarti Erry Prasmatiwi; Hurip Santoso (Lampung University, 2014)
This study aims to: (1) analyze the production’s efficiency of chilli in East Lampung Regency (2)determine the factors influencing the technical efficiency of chilli farm in East Lampung Regency,and (3) determine the amount of chilli farming income in East Lampung Regency. The research locatedin East Lampung Regency by selecting purposively two village namely Kibang and Margototo. Farmerssample were done randomly by using sample random sampling method, with a total sample are 60chilii’s farmers. Data collection did on April till May 2013. The analysis that was used in this researchis descriptive and quantitative analysis. The First purpose was answered by using frontier productionfunction, the second purpose using multiple linear regressing analysis and the third purpose wasanswered by using income analysis.The results showed that (1) chilli farming in East LampungRegency was not technically efficient, technical efficiency of farming in East Lampung Regency was81,01 %, (2) the factors that influence significantly in technical efficiency of chilli farm in EastLampung Regency was scale farming, income, and risk.(3) farm chilli in East Lampung Regency wasa profitable farming because it has a value of R/C more than one that is aqual to 2,78 with income Rp54.674.270,53/ha.Key words: chilli farming, frontier production functio, technical efficiency